Understanding How Local Food Experiences and Cultural Competence Influence Culinary Tourist Behavior - Sesilya Kempa; Felix Hartono; Devi Destiani Andilas (Master of Management, School of Business and Management, Petra Christian University, 2025)
Traditional cuisine is a cultural element with significant potential for driving tourism development, making understanding the psychological mechanisms that influence tourist intentions crucial. Four dimensions of experience—novel, authentic, sensory, and social experience—were examined to determine how each contributed to the formation of behavioral intentions through cultural competence. Data were collected from 101 domestic tourists who had visited Surakarta as a sample and analyzed using SmartPLS 4.0. The results showed that sensory and social experiences significantly influenced behavioral intention through increased cultural competence. Conversely, novel and authentic experiences did not show a significant mediating effect. These findings emphasize the importance of optimizing sensory and social aspects in designing Surakarta culinary tourism experiences and offer managerial implications for developing culture-based destination strategies.